Finite element analysis of clamped circular sandwich plates under bending - Uthayan Sritaran (2010)
Now in current world design applications in automotive, aerospace and military, cellular solids such as foams either in regular lattice or irregular structures is widely being used. This is due to their light weight, strong and stiff design capabilities. Compressive response of these materials’ is exploited for designing energy management devices. Formations of sandwich panels are by joining cellular materials with strong and stiff materials. Properties of sandwich panel are of high strength, excellent energy absorption and light weight. The main disadvantage of cellular structures is very sensitive to localized load and indentation is the most dominating failure modes.